FAKTOR - FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2013-2015) - Erliva Oktavita, 11.05.52.0016; Indarti, MG. Kentris (Students Journal of Accounting and Banking, 2016)
The purpose of this study was to analyze the influence of return on assets, return on equity, current ratio, debt to asset ratio, debt to equity ratio, total asset turnover ratio against financial distress in companies listed on the Stock Exchange Year 2013-2015. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange (BEI). The sample in this study as many as 101 companies. The sampling technique used purposive sampling. The criteria for the sample in this study is melaporakn companys financial statements, the company uses Rupiah and companies that have complete data. The analysis tool used is logistic regression. The results of the analysis can be concluded that: Return on assets significantly negative effect on the likelihood of financial distress. Return on equity does not significantly influence financial distress. Current ratio does not significantly affect the likelihood of financial distress. Debt to total assets ratio is a significant positive effect on the likelihood of financial. Debt to equity ratio is a significant positive effect on the likelihood of financial distress. Total asset turnover ratio significantly negative effect on the likelihood of financial distress. Â Keywords: Return on Assets, Return on Equity, Current Ratio, Debt to Asset Ratio, Debt to Equity Ratio, Total Asset Turnover Ratio, Financial Distress